Observations upon the economic effects of absenteeism on Ireland - Maley, A. J. (Statistical and Social Inquiry Society of Ireland, 1851)
There are few questions generated by the peculiar condition of Ireland more interesting to its people, than that upon which I am about to offer a few observations; for if the opinion which I, in common with many others, hold, that the nonresidence in Ireland of those who, as landlords or creditors, receive the amount of rents payable out of lands in it, is injurious to this country, be not well founded, there is a prevalence of error amongst us that cannot but operate injuriously upon the Irish community, by creating false notions as to what many of us regard as one of the principal causes of our poverty, and one of the greatest impediments to the improvement of our condition; and if, on the other hand, the doctrine we hold be sound, it is not less important that the error of those who entertain a contrary opinion should be corrected. For although it may not be practicable to remedy the evils resulting from absenteeism, by compelling Irish proprietors to live in Ireland, the pernicious influence of their absence upon the prosperity of the country, in an economic, as well as in a social, point of view, ought to be mitigated by those who have it in their power to do so; because it is an evil which we are obliged to suffer to a great extent for the benefit of our British fellow-subjects, and as the result of our political relations with them, and therefore we ought to be compensated for its endurance by the enjoyment of some countervailing good.
Read March 18th 1850
Keywords: Absentee landlords; 314.15